Exploring and building autism service capacity in rural and remote regions: Participatory action research in rural Alberta and British Columbia, Canada. (July 2019) - Young, Amber; Nicholas, David B; Chamberlain, Shirley-Pat; Suapa, Nirach; Gale, Nancy; Bailey, Anthony J
Based in participatory action research, this project had the aim of building capacity in treatment and support for individuals and families impacted by autism spectrum disorder in remote and rural communities of Canada. Communities were selected based on their rurality and willingness to engage in change efforts for enhanced service delivery within their region. Fifteen discussion groups with key stakeholders were convened in seven communities with 200 community stakeholders. Based on analyses of these data from the stakeholders, themes were distilled through interpretive description, which in turn were presented to community stakeholders for reflection and collective action. Findings indicate broad thematic domains consisting of: insufficient services, protective factors in community, change efforts via collectivity within community, limitations and benefits of residing in rural communities relative to care associated with autism spectrum disorder, a sense of "community" in rural contexts, and engaging in focused dialogue as a pathway to advancement. Opportunities for building capacity for support in autism spectrum disorder emerged within intersecting layers of leadership, contextual factors, and community collaboration. Consistent with participatory action research principles, emerging local knowledge was supported with strategies for improved autism spectrum disorder service development.